2013
DOI: 10.5142/jgr.2013.37.355
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of ginseng cultivated under mountainous forest with different growing years

Abstract: Ginseng cultivated and grown naturally under mountainous forest is formally called “Lin-Xia-Shan-Shen” (LXSS) and grown in manual condition is called garden ginseng (GG) according to Chinese pharmacopoeia (2010 edition). Usually the growing condition of LXSS is similar to wild ginseng and mostly used in Chinese folks in ancient times. The antioxidant properties of LXSS with different growing years were evaluated by their inhibitions of thiobarbituric acid-reactive substance (TBA-RS) formation in liver homogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 4 publications
(4 reference statements)
1
22
0
Order By: Relevance
“…3), indicate that phenolic compounds that are stronger than ginsenoside also contribute to the antioxidant potential of the P. quinquefolium cell cultures. Our results confirm the findings of previous studies, which indicate that phenolic compounds are the main antioxidant components in plants and that their level is closely related to the plant antioxidant potential [35,37]. Similar observations were made for ginseng roots grown under different conditions; phenolic compounds were found to have a stronger influence on antioxidant activity than saponins [17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3), indicate that phenolic compounds that are stronger than ginsenoside also contribute to the antioxidant potential of the P. quinquefolium cell cultures. Our results confirm the findings of previous studies, which indicate that phenolic compounds are the main antioxidant components in plants and that their level is closely related to the plant antioxidant potential [35,37]. Similar observations were made for ginseng roots grown under different conditions; phenolic compounds were found to have a stronger influence on antioxidant activity than saponins [17].…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that the antioxidant properties can be related to the levels of phenolic compounds and ginsenosides in naturally-grown plant material [7,[35][36][37]. The present study is the first to evaluate both the ginsenoside and total phenolic compound contents in P. quinquefolium cell culture extracts and determine their antioxidant capacity.…”
Section: Discussionmentioning
confidence: 82%
“…The radical scavenging activity of A. asiatica and eupatilin against DPPH was determined spectrophotometrically. In microwells, 100 μ L of an aqueous solution of the completely dissolved sample (control: 100 μ L DW) was added to an ethanolic solution of DPPH (100 μ L, 60 μ M) according to the reported method [ 25 ]. The final concentrations of the tested samples in the assayed solution were 10, 25, 50, and 100 μ g/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of ginsenosides and amino acids in wild ginseng are much higher than those of cultivated ginseng. Wild ginseng also reported to have enhanced host defense components and biological activities (Pan et al, 2013;Sun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%